Exploring the Experiences of Third Culture Kids in Multiple Educational Contexts : A Focus on Socialization - Niemelä, Johanna (My University, 2021)
This study explores Third Culture Kids (TCKs) and their educational experiences. Third Culture Kids are defined as people who have lived in a country other than their own during their developmental years (1-18). Due to their transient upbringing, Third Culture Kids are often exposed to a number of different educational experiences and settings, ranging from local, international school, and boarding schools to homeschooling. Drawing from the interviews of ten Adult Third Culture Kids (ATCKs), this study will explore the past social educational experiences of TCKs between the ages of one to eighteen situated primarily within international schools, local schools, and homeschooling environments. A reflexive timeline was utilized as a way to measure the life trajectories and educational influences of TCKs. Findings indicated that TCKs are subject to unparalleled, contrasting and oftentimes challenging social experiences in the educational environments. Each educational setting is marked by distinct interactions with peers, educators and the learning environment, which determine the success of TCKs’ educational experiences. For the most part, international schools continue to be the favorable schooling destination for Third Culture Kids. Implications for teachers, school counsellor and parents are also discussed in the study.
Keywords: Third Culture Kids, third culture, schooling, international schools, local schools, homeschooling, relationships, educators, teachers, counsellors and the learning environment.